2017
DOI: 10.1097/ccm.0000000000002051
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Level Changes in Adult ICU Bed Supply in the United States

Abstract: Objective Although the number of intensive care beds in the United States is increasing, little is known about the hospitals responsible for this growth. We sought to better characterize national growth in intensive care beds by identifying hospital-level factors associated with increasing numbers of intensive care beds over time. Design We performed a repeated-measures time series analysis of hospital-level intensive care bed supply using data from Centers for Medicare and Medicaid Services. Setting All U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 42 publications
1
43
0
1
Order By: Relevance
“…Arguably, sustained strain contributes to inefficient and inequitable utilization of finite ICU resources. While opening additional ICU beds may seem the simplest response, this is not necessarily sustainable, and likely only a short-term reprieve [ 29 ]. Rather, in order to explain the breadth of effect strain may have on patients, professionals and operations, a constellation of evidence-informed quality indicators are likely to be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, sustained strain contributes to inefficient and inequitable utilization of finite ICU resources. While opening additional ICU beds may seem the simplest response, this is not necessarily sustainable, and likely only a short-term reprieve [ 29 ]. Rather, in order to explain the breadth of effect strain may have on patients, professionals and operations, a constellation of evidence-informed quality indicators are likely to be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…3 Another study of more than 4,400 hospitals found a significant increase in the number of adult intensive care beds between 2009 and 2011, but this growth was seen mostly in large urban teaching facilities, rather than in rural areas or smaller, less-resourced hospitals, which often serve residents with little or no other access to care. 4 In addition, there has been an increase in the number of rural hospitals closing each year. 5 During a public health emergency, federal, state, or local stockpiled ventilators should be deployed in a way that optimizes the effectiveness, efficiency, and equity of this scarce resource.…”
mentioning
confidence: 99%
“…6,7,9 Upon examining this new model, we observed that the highest tier ICU bed adjustment (≥43 ICU beds) was lower than the number of ICU beds at many large US hospitals, and there was no adjustment for oncology units and/or hematopoietic cell transplant units (ONC-HCT units) within general hospitals, despite wide recognition that these patient populations are at increased risk for CDI (Table 1). 6,10 We hypothesized that inadequate adjustment for these patients might explain why large, academic hospitals tend to be poor performers in CDI SIR rankings and decided to investigate the effect of removing ICU and ONC-HCT unit data on the CDI SIRs of large, general, acute-care facilities. [11][12][13]…”
mentioning
confidence: 99%